2019
DOI: 10.3390/agronomy9060331
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Effects on Mineral Nitrogen Leaching, Moisture Content, and Evapotranspiration after 15N Urea Fertilization for Vegetable Crop

Abstract: Globally, mineral nitrogen (N) losses as nitrate leaching (NL) are a substantial portion of applied fertilizer and cause surface and sub-surface water contamination. To precisely measure NL and its interlink parameters, biochar soil amendment was tested in this study. Three treatments—biochar (BC), without biochar (WB) with 15N urea (300 kg/ha), and control (no fertilization)—were tested in soil-filled lysimeters (circular PVC (Polyvinyl Chloride) tank of 30 cm diameter and 35 cm height) equipped with moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…However, it could be shown that the addition of Bc (biochar) to the soil substrate led to a significant increase in the biomass production of M. ciliaris in both water regimes (see also Sensitivity index in Table 1). Similar Bc effects were reported for rice and maize grain yields (increase of 12.1% and 28% respectively) [71][72][73].…”
Section: Adjustment Of Growth and Water Relationssupporting
confidence: 84%
“…However, it could be shown that the addition of Bc (biochar) to the soil substrate led to a significant increase in the biomass production of M. ciliaris in both water regimes (see also Sensitivity index in Table 1). Similar Bc effects were reported for rice and maize grain yields (increase of 12.1% and 28% respectively) [71][72][73].…”
Section: Adjustment Of Growth and Water Relationssupporting
confidence: 84%
“…Our study showed that the NH 4 + -N contents of tillage soil increased with the increase in BC application. Previous results by Ahmad et al [ 28 ] showed that the N mineralization rate in soil was enhanced by BC application, which explained the increase in NH 4 + -N contents due to BC addition in the present experiment. In addition, the results of our experiment showed that, in the 0–10 cm soil profile, the NH 4 + -N and NO 3 − -N contents under the treatment with added BC were higher, while, at the deeper soil profile, the NH 4 + -N and NO 3 − -N contents under the BC treatment were lower than those measured under the N fertilizer-only treatment, and this pattern was even more significant at the low N level.…”
Section: Discussionsupporting
confidence: 73%
“…Our study showed that the NH 4 + -N contents of tillage soil increased with the increase in BC application. Previous results by Ahmad et al [28] showed that the N mineralization rate in soil was enhanced by BC application, which explained the increase in NH 4…”
Section: Soil Propertiesmentioning
confidence: 86%
“…It also stabilizes soil carbon, enhances nitrogen uptake, decreases mineral nitrogen leaching, increases electrical conductivity, water availability, and water use efficiency. This enhances soil nutrient availability and tolerance to abiotic stresses [56,57,11,58]. Biocharmediated soil improvements significantly enhance photosynthetic activity, chlorophyll synthesis, gene expression, stress-responsive proteins, and hormonal balance.…”
Section: Proline Contentmentioning
confidence: 99%